PENGARUH TINGKAT PENDIDIKAN ORANG TUA TERHADAP KARAKTER JUJUR ANAK DI DUSUN SUKASARI KELURAHAN KAMPUNG REMPAK KECAMATAN SIAK KABUPATEN SIAK - Rapita '; Gimin '; Supentri ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by issues arising from interviews conducted by the researcher is that the children does not have the personality or character of agood honest. The parents that have higher education or have studied better able to guide and direct their children to instill good character, one of the character is honest, compared with parents who studied low.The purpose of this research is to determine the effect of parental educational level to the children in sukasari kampung rempak siak. The method of this research is using descriptive analysis of quantitative , data analysis with the simple linear regression. Based on the result of this research concluded that the percentage of the recapitulation of the answer to the questionnaire respondents about the influence of parental educational level of the character of an honest children in sukasari kampung rempak siak, education level of parent ( father and mother ) variables x belonging to secondary education that is equal to 47,82 %, whereas for honest character variable y with the answer very often by 30,25 %, often is equal 54,7 %. Based on bencmarks in chapter III that the number who answered very often + often by 84, 95 % in the range 75,01 % - 100,00 % or excellent means children in sukasari kampung rempak siak have a very good honest character with a percentage of 84,95 % which means that the higher the education level of parents, the better similarly onest character children in sukasari kampung rempak siak. Based on research result, the authors recommend to he public is expected to continue education, so as to create a generation of honest and useful for the homeland of the nation and the state, because educated parents is easier to guide and direct his honest character.Keyword : education level of parents, honestly character